Broad electricity price subsidies for industry are not a suitable relief instrument - Lea Bernhardt; Tomaso Duso; Robin Sogalla; Alexander Schiersch (DIW Weekly Report, 2023)
The sharp rise in electricity prices has led to a discussion on possible subsidies for companies in the form of an industrial power tariff. The subsidies should help companies remain internationally competitive and prevent them from relocating overseas. Although German electricity prices for (industrial) firms are around the European average due to many tax exemptions, they are significantly higher compared to other non-European countries. Simulations using price increases of different magnitudes show that only a small share of companies would face major price increases compared to their value added. Moreover, there is considerable heterogeneity between the sectors. For example, the industrial gases or aluminum production sectors would be much more affected than other sectors. Thus, a large-scale industrial electricity price subsidy does not seem to be very effective. Selective relief for certain sectors may be problematic under competition law and may need to be granted well beyond the temporary nature of the subsidy.
Keywords: H2; K32; L5; Q4; 330; energy costs; subsidy; competition policy